Review of the distribution and conservation of Far Eastern Curlew Numenius madagascariensis in the River Lena and River Yana basins, East Siberia - Degtyarev, Victor G. (Wildfowl, 2022)
The catchments of the River Lena and River Yana are the least known parts of the nesting grounds of the endangered Far Eastern Curlew Numenius madagascariensis, despite accounting for almost half of its known breeding range. This analysis reports on the current distribution of the Far Eastern Curlew, delineates the northern and western extent of its breeding range and describes distribution patterns and threats to the species, based on field research, reports from local people, and a review of historical and most recent publications. The breeding grounds extend to 63°17’N–67°31’N latitude north and 112°27’E–135°11’E longitude west, with the western bow-shaped limit extending to the middle reaches of the River Aldan. The only non-mountainous part of its breeding range within the Lena and Yana River basins is in a 700 × 300 km area west of the Verchoyanskiy Range (63°–66°N), which suggests that the Far Eastern Curlew is a species of mountainous and sub-montane areas. Depending on habitat mosaics, breeding curlews are sparsely distributed in solitary pairs, concentrated in mountains and their foothills. Data are lacking to support the estimation of regional trends in the abundance and distribution of Far Eastern Curlews. Annual hunting of the species does not appear to be critical, and the species is not susceptible to any other obvious threats. The Far Eastern Curlew is able to breed successfully in wetlands subject to human disturbance, but the pristine state of the majority of the breeding grounds and the low-level human activities within its core range suggest predominantly favourable conditions and a general lack of critical direct threats to the species in the River Lena and River Yana catchment areas.